Numerical Computation of MHD Thermal Flow of Cross Model over an Elliptic Cylinder: Reduction of Forces via Thickness Ratio. (18th October 2021) - Majeed, Afraz Hussain; Mahmood, Rashid; Abbasi, Waqas Sarwar; Usman, K.
Abstract : The present work is concerned with a comprehensive analysis of hydrodynamic forces, under MHD and forced convection thermal flow over a heated cylinder in presence of insulated plates installed at walls. The magnetic field is imposed in the transverse direction of flow. The Galerkin finite element (GFE) scheme has been used to discretize the two-dimensional system of nonlinear partial different equations. The study is executed for the varying range of flow behavior index n from 0.4 to 1.6, Hartmann number Ha from 0 to 100, Reynolds number Re from 10 to 50, Grashof number Gr from 1 to 10, thickness ratio e from 0.5 to 1.0, and Prandtl number Pr from 1 to 10, respectively. A coarse hybrid computational grid is developed, and further refinement is carried out for obtaining the highly accurate solution. The optimum case selection is based on flow patterns, drag and lift coefficients, and pressure drop reduction against cylinder thickness ratios and average Nusselt numbers. Drag coefficient increases with an increase in thickness ratio e . The drag force reduction for e = 0.5 and e = 0.75 is also observed for a range of the power law index as compared with e = 1.0 cylinder. Maximum pressure drop over the back and front points of cylinder is reported at Ha = 100 .